Synthesis of isoxazolidine and isoxazoline rings via 1,3-dipolar cycloaddition reaction tethered to 2-benzothiazolethiol and study their antibacterial activity - Alkayar, Ziad T I; Ibrahim, Zena Tariq; Hassan, Huda F.; Ali, Enas Sami (Edelweiss Applied Science and Technology, 2025)
New 2-benzothiazolethiol derivatives containing isoxazolidine and isoxazoline rings were made throughout 1,3-dipolar cycloaddition reactions. 4-methyl-o‐phenylenediamine was treated with carbon disulfide to form benzo[d]thiazole-2-thiol 1. The S-alkylation reaction of thiol group using allyl bromide and propargyl bromide gave compounds 2 and 3 in 83% and 90% yields respectively. Then, freshly prepared nitrones which are obtained in stiu by the reaction of N-methylhydroxylamine with deferent substituted aromatic aldehydes; 4-hydroxybenzaldehyde, 4-hydroxy-1-naphthaldehyde, 5-Methyl-2-thiophenecarboxaldehyde, 3-nitrobenzadehyde and 3-bromorobenzaldehyde, then, were reacted with compounds 2 and 3 which gave compounds 4a-e and 5a-e containing isoxazolidine and isoxazoline rings respectively. All the obtained compounds were characterized using infrared (IR) spectroscopy and Nuclear Magnetic Resonance (NMR) spectrophotometer and all were very matched the data of the structure. Gram-negative (Escherichia coli, Pseudomonas aeruginosa) and gram-positive (Bacillus subtilis, Staphylococcus aureus) bacteria were used to evaluate the anti-bacterial activities for the obtained compounds, and the results displayed significant activity towards the selected bacteria by comparison to the standard drug amoxicillin.